Технологія виготовлення глиняного посуду у VІІ — на початку ІІІ ст. до н. е. в Дніпровському лісостеповому Лівобережжі - Гейко, А.В. (Археологія і давня історія України, 2011)
Стаття знайомить з проторемісничим процесом виготовлення глиняного посуду скіфського часу, починаючи від заготовки глини і кінчаючи його декоруванням та випалом. Статья посвящена технологии изготовления лепной посуды скифского времени в Днепровском лесостепном Левобережье. Прослежены все этапы ее изготовления — от подбора глины до обжига. Экономические условия, домашнее изготовление, натуральное хозяйство и натуральный обмен, отсутствие специализации в гончарстве не давали существенных стимулов для ускоренного перехода гончарного производства от домашнего изготовления к ремеслу. Этот процесс затянулся и был прерван многочисленными потрясениями в начале ІІІ в. до н. э. The article deals with the investigations is devoted to the complex studying of the hand-modelled pottery of the Scythian epoch of the tribes of Dnipro Left-Bank Forest-Steppe Region. The author traces out all the phases of pottery-making, beginning with the selection of clays and concluding with firing. The author determines the economic level of pottery craft. It was ascertained, that the domination of natural economy and barter, the absence of specialization in pottery craft did not provide any stimuli for the development of pottery craft in the direction of its rapid conversion from home manufacture to the handicraft. This process has been delaying and was ceased in the early third century BC by the different changes and upheavals in the social and economic life of the tribes of Dnipro Left-Bank Forest-Steppe Region.